Production of Ramoplanin and Ramoplanin Analogs by Actinomycetes - de la Cruz, Mercedes; González, Ignacio; Parish, Craig A.; Onishi, Russell; Tormo, José R.; Martín, Jesús; Peláez, Fernando; Zink, Debbie; El Aouad, Noureddine; Reyes, Fernando; Genilloud, Olga; Vicente, Francisca (Frontiers in Microbiology, 2017)
Ramoplanin is a glycolipodepsipeptide antibiotic obtained from fermentation of Actinoplanes sp. ATCC 33076 that exhibits activity against clinically important multi-drug-resistant, Gram-positive pathogens including vancomycin-resistant Enterococcus (VRE), methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-intermediate resistant Clostridium difficile. It disrupts bacterial cell wall through a unique mechanism of action by sequestering the peptidoglycan intermediate Lipid II and therefore does not show cross-resistance with other antibiotics. However, while demonstrating excellent antimicrobial activity in systemic use in animal models of infection, ramoplanin presents low local tolerability when injected intravenously. As a consequence of this limitation, new derivatives are desirable to overcome this issue. During a natural product screening program developed to discover compounds that disrupt bacterial cell wall synthesis by inhibiting peptidoglycan transglycosylation through binding to the intermediate Lipid II, 49 actinomycete strains were identified by HR-LCMS as producers of ramoplanin-related compounds. The producing strains were isolated from environmental samples collected worldwide comprising both tropical and temperate areas. To assess the diversity of this microbial population, the 49 isolates were initially identified to the genus level on the basis of their micromorphology. This analysis resulted in the identification of members of genus Streptomyces, as well as representatives of the families Micromonosporaceae, Nocardiaceae, Thermomonosporaceae and Pseudonocardiaceae, suggesting that the production of ramoplanins is relatively widespread among Actinomycetes. In addition, all of these isolates were tested against a panel of Gram-positive and Gram-negative bacteria, filamentous fungi and yeast in order to further characterize their antimicrobial properties. This work describes the diversity of actinomycete strains that produced ramoplanin-related compounds, and the analysis of the antimicrobial activity exhibited by these isolates. Our results strongly suggest the presence of new ramoplanin-analogs among these actinomycete producers. Current large scale fermentations and purifications are being performed for the identification of these novel antimicrobials.